Republic of Kosovo : Technical Assistance Report-Financial Sector Stability Review. (IMF Staff Country Reports; Country Report ;, 2020)
The FSSR mission team conducted a diagnostic review of CBK governance and of the financial system, undertook a stocktaking of the implementation of recommendations from the 2012 Financial Sector Assessment Program (FSAP) and MCM TA, and proposed a TA Roadmap to support the efforts of the authorities to address key gaps and vulnerabilities. The IMF Statistics Department (STA) supported the mission with an assessment of the compilation of financial soundness indicators (FSIs), monetary and financial statistics, and balance sheet matrices (Annex I).